Bone formation without lamina dura in the middle-aged and elderly: possible dependence on enamel - Minoru Yamaoka (Clinical Interventions in Aging, 2010)
Minoru Yamaoka1, Masahide Ishizuka1, Kohji Ishihama1, Masahiro Takahashi1, Miho Takahashi1, Hidefumi Yamada1, Yuji Teramoto1, Kouichi Yasuda1, Toshikazu Shiba2, Takashi Uematsu1, Kiyofumi Furusawa11Matsumoto Dental University, Oral and Maxillofacial Surgery, Shiojiri, Nagano, Japan; 2Regenetiss Co., Koganei, Tokyo, JapanAbstract: Bone formation below the crown of mandibular horizontal incompletely impacted third molar is frequently seen in the middle-aged and elderly. The phenomenon shows lamina dura loss without radiolucency and we hypothesized the participation of mature enamel without any influence on the environmental oral status. In order to investigate the characteristics of the phenomenon based on the presence/absence of the lamina dura and radiolucency below the crown, we studied the relationship between 58 men and 43 women with a lamina dura without radiolucency, 12 men and 8 women without a lamina dura with radiolucency, 34 men and 16 women without a lamina dura without radiolucency, and the status of teeth in the ipsilateral mandible. Subjects without a lamina dura without radiolucency were significantly older than those with a lamina dura without radiolucency in both men (P < 0.0001) and women (P < 0.01), indicating different chronological causes. Men without lamina dura with radiolucency showed significantly more tooth loss than those with a lamina dura without radiolucency (P < 0.00001) and those without a lamina dura without radiolucency (P < 0.0001), indicating the influence of poor oral health. Thus, the phenomenon without a lamina dura without radiolucency may show the clinical importance of bone formation in the elderly.Keywords: bone formation, lamina dura, enamel, elderly